Особенности политической культуры при постсоветских интеграционных и демократизационных процессах (Քաղաքական մշակույթի առանձնահատկությունները հետխորհրդային ինտեգրման և ժողովրդավարացման գործընթացներում) - Օրդուխանյան Էմիլ (YSU Journal of International Affairs, 2017)
The article explores the features of political culture in integration and democratization processes in post-Soviet countries using the comparative method of analysis. After the collapse of the Soviet Union, a new process of transformation has started. Recent research has shown that during this period several peculiarities have proved that post-Soviet transformation is exceptionally a complex and multi-vector process. All these countries declared democracy values as a top priority but actually, only a part of them was able to build more or less a democratic regime. Especially these countries are those which have chosen the way of European integration. Meanwhile, in other post-Soviet countries which have preferred Eurasian integration or stayed outside, there are still many challenges to democracy they need to overcome. In the framework of research, the article also explores the features of political culture and its impact on integration and democratization processes in post-Soviet countries. Finally, we conclude that consociational democracy model can be a useful tool to democratization for some post-Soviet countries with plural societies.